2019
DOI: 10.1097/phm.0000000000001250
|View full text |Cite
|
Sign up to set email alerts
|

Does Performance on the American Board of Physical Medicine and Rehabilitation Initial Certification Examinations Predict Future Physician Disciplinary Actions?

Abstract: Objective The aim of the study was to determine the relationship between performance on the American Board of Physical Medicine and Rehabilitation primary certification examinations and the risk of subsequent disciplinary actions by state medical boards over a physician's career. The hypothesis is that physicians who do not pass either or both of the two initial specialty certification examinations are at higher risk of disciplinary action from a state medical licensing board. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
20
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(20 citation statements)
references
References 13 publications
0
20
0
Order By: Relevance
“…20 Scores on certi cation exams were associated with discipline risk, with lower scores having a higher risk of future disciplinary action. 66,67,75,85 Board-certi ed physicians also were less likely to receive a severe penalty and more likely to receive a less severe penalty. 33,67,73,75,89 One study found that higher scores on the board certi cation exam reduced the likelihood of disciplinary action for both domestic and international graduates, but that it was more protective against disciplinary action for domestic graduates than for international graduates.…”
Section: Board Certificationmentioning
confidence: 98%
See 4 more Smart Citations
“…20 Scores on certi cation exams were associated with discipline risk, with lower scores having a higher risk of future disciplinary action. 66,67,75,85 Board-certi ed physicians also were less likely to receive a severe penalty and more likely to receive a less severe penalty. 33,67,73,75,89 One study found that higher scores on the board certi cation exam reduced the likelihood of disciplinary action for both domestic and international graduates, but that it was more protective against disciplinary action for domestic graduates than for international graduates.…”
Section: Board Certificationmentioning
confidence: 98%
“…Research on whether being an international graduate increases risk of future disciplinary action is con icting. Nine studies 15,16,24,35,62,66,69,109,112 and two review articles 33,91 found that international graduates were at higher risk of disciplinary action than domestic graduates, and one found an increased odds ratio for discipline with overseas training but it was not statistically signi cant. 90 Another study found that international graduates were more likely to receive high impact decisions in every stage of the disciplinary process and were more likely to be suspended or have their license revoked.…”
Section: Common Reasons For Disciplinary Actionmentioning
confidence: 99%
See 3 more Smart Citations